Landing techniques in volleyball - Lobietti, R.; Coleman, S.; Pizzichillo, E.; Merni, F. (Journal of Sports Sciences, 2010)
Knee injuries such as anterior cruciate ligament lesions and patellar tendonitis are very frequent in volleyball, and are often attributed to micro traumas that occur during the landing phase of airborne actions. The aim of the present study was to compare different jumping activities during official men's and women's volleyball games. Twelve top-level matches from the Italian men's and women's professional leagues were analysed. The jumps performed during the games were classified according to the landing technique used by the player (left or right foot or both feet together), court position, and ball trajectory. Chi-square analyses were performed to detect differences in landing techniques between the sexes, court positions, and trajectories when serving, attacking, blocking, and setting. Significant differences (P < 0.05) were found between the sexes for block, set, and spike but not for the jump serve. The frequency of landings on one foot was related to court position and the trajectory of the sets: when spiking faster sets, the players were more likely to use a one-footed landing. The present results should help coaches and physiotherapists to devise appropriate training and prevention programmes, and reveal the need for further detailed biomechanical investigations of the relationships between landings and knee injuries.